2019
DOI: 10.18174/476849
|View full text |Cite
|
Sign up to set email alerts
|

Urban food security in Ghana: a policy review

Abstract: This policy review aimed (i) to investigate how urgencies such as urbanisation and climate change are recognised in the current policies of a low-income country, and (ii) to investigate how food security, and urban food security in particular, interacts with these policies. Ghana is used as an example. The policy review revealed that the agricultural, nutrition and health, spatial development and climate policies dealt with one or more aspects of food security within the food system framework. The overall conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…When it comes to adolescents' exposure to unhealthy diets, the policy environment is one of the most underresearched domains. There are existing policies in Ghana that speak to various aspects of food security; a recent policy review found 23 policy documents that either mention or are centred on food and nutrition security, from poverty reduction and economic development, to agriculture, nutrition and health, spatial demographic development, climate change, and trade (Linderhof et al, 2019). Examples include Food and Agriculture Sector Development Policy (Ministry of Food & Agriculture, 2007), and Support to the Planting for Food and Jobs Campaign (FAO, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to adolescents' exposure to unhealthy diets, the policy environment is one of the most underresearched domains. There are existing policies in Ghana that speak to various aspects of food security; a recent policy review found 23 policy documents that either mention or are centred on food and nutrition security, from poverty reduction and economic development, to agriculture, nutrition and health, spatial demographic development, climate change, and trade (Linderhof et al, 2019). Examples include Food and Agriculture Sector Development Policy (Ministry of Food & Agriculture, 2007), and Support to the Planting for Food and Jobs Campaign (FAO, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For the improvement of food security in Accra and Ghana, the emphasis of Ghana's policy has largely been the improvement of food availability in terms of increasing agricultural production and setting productivity targets (Linderhof et al 2019). The policy review of Linderhof et al (2019) aimed to provide insight into how urban food security was incorporated in four polices: agricultural policy, nutrition and health policy, economic policy and spatial planning policy. In their policy review on urban food security, they used the four pillar of food security as defined by the FAO: food availability, food accessibility, food utilisation and stability.…”
Section: Policiesmentioning
confidence: 99%